Effect of practicum courses on pre-service teachers' beliefs towards chemistry teaching: a year-long case study. Issue 3 (29th April 2019) - Boz, Yezdan; Ekiz-Kiran, Betul; Kutucu, Elif Selcan
Abstract : In this study, we examined the effect of School Experience (SE) and Practice Teaching (PT) courses on pre-service chemistry teachers' beliefs towards chemistry teaching over a one-year period. To reach this purpose, participants' beliefs and experiences towards chemistry teaching were monitored closely throughout the varied phases of the two practicum courses. Two pre-service chemistry teachers participated in the study. Data were collected via semi-structured interviews, observation notes, CoRes and reflection papers. Semi-structured interviews focusing on the pre-service teachers' beliefs regarding chemistry teaching were conducted three times while participating in the SE and PT courses. During the PT course before their teaching experiences the participants prepared CoRes, and after their experiences they critiqued their own performances. Moreover, the participants were observed during their student-teaching experiences to identify how they transfer their beliefs into their teaching. Data were analyzed via inductive analyses. Results indicated that both pre-service teachers had stable core beliefs derived from their own experiences as students that remained constant during these courses and guided their practical instruction. Although both participants attended the same courses during the teacher education program, their attitudes while taking the educational courses were different. Factors that shaped pre-service teachers' beliefs towards teaching were presented as the practicum courses enriched with CoRes and reflection papers, observing their mentors, experiences gained from microteaching sessions, and pedagogical and methods courses taken during the pre-service teacher education program. Implications for the formation of pre-service teachers' beliefs towards teaching throughout pre-service teacher education programs were provided.